2010
DOI: 10.1002/em.20596
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation of CpG sites in two isoforms of myosin binding protein C, an important hypertrophic cardiomyopathy gene

Abstract: Hypertrophic cardiomyopathy (HCM) is a common form of cardiac disease. Over 400 causative mutations have been identified in 20 sarcomere and myofilament related genes. The high density of mutations found in genes associated with HCM may suggest that mechanisms promoting increased mutability play a role in disease prevalence. The objective of this study was to evaluate the CpG methylation level of the exonic regions of the cardiac myosin binding protein C gene (MYBPC3), a common causal gene for HCM. To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…DNA methylation in single genes and its contribution to disease onset or progression has been demonstrated in studies for hypertrophic cardiomyopathy (Meurs & Kuan, 2011). Furthermore, Movassagh et al (Movassagh et al, 2011) reported distinct epigenomic features in explanted human failing hearts, highlighting a potential role of DNA methylation also in end‐stage heart failure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…DNA methylation in single genes and its contribution to disease onset or progression has been demonstrated in studies for hypertrophic cardiomyopathy (Meurs & Kuan, 2011). Furthermore, Movassagh et al (Movassagh et al, 2011) reported distinct epigenomic features in explanted human failing hearts, highlighting a potential role of DNA methylation also in end‐stage heart failure.…”
Section: Discussionmentioning
confidence: 96%
“…Disease modification through epigenetic alterations has been convincingly demonstrated for a number of diseases (Feinberg & Tycko, 2004; Jones & Baylin, 2002). In the cardiovascular system, histone modifications and chromatin remodelling are thought to direct adaptive as well as maladaptive molecular pathways in cardiac hypertrophy and failure (Montgomery et al, 2007), and DNA methylation was found to be responsible for the hypermutability of distinct cardiac genes (Meurs & Kuan, 2011). Furthermore, recent studies have highlighted potential interplay between environmental factors and the disease phenotype by epigenetic mechanisms (Herceg & Vaissiere, 2011; Jirtle & Skinner, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, DNA methylation was found to be responsible for the hypermutability of distinct cardiac genes. This is the case for the cardiac isoform of the myosin binding protein C gene (Mybpc3) that has a significantly higher level of exonic methylation of CpG sites than the skeletal isoform (Mybpc2; Meurs and Kuan, 2011). This suggests that there are unique aspects of the Mybpc3 gene or its epigenetic environment that are prone to generate genetic mutations.…”
Section: Epigenetic Control Of Heart Failurementioning
confidence: 99%
“…Considering that epigenetic alteration in HOPX gene promoter was found related to some cancers (42,43), and that methylation level in exonic CpG sites of cardiac MYBPC3 gene, a common causal gene for HCM, may result in increased genetic mutability (44), epigenetic evaluation of HOPX gene promoter is wothy of investigation in HCM patients.…”
Section: Discussionmentioning
confidence: 99%